The Relationship Between School Well-Being with Online Learning Motivation During the Covid-19 Pandemic in Psychology Students - Aphroditha Salsabilla Renjaan; Dewi, Eva Maizara Puspita; Nur Akmal (PT FORMOSA CENDEKIA GLOBAL, 2023)
The role of school well-being and learning motivation is one of the factors that become success in the application of online learning. This study aims to find out how the relationship between school well-being with learning motivation in online learning. This research involved 325 students of the Faculty of Psychology, Makassar State University. This study used a simple random sampling technique to select samples from the population. The data obtained are analyzed using product moment analysis techniques. The results of the study found a positive and significant relationship between school well-being and learning motivation (r = 0.507; p = 0.000). Other findings in the study showed that by gender there was no significant difference in learning motivation score outcomes, and there were significant differences in school well-being outcomes. The results of this study show a fairly strong level of correlation, so that the higher the school well-being experienced by active students of the Faculty of Psychology, Makassar State University, the higher the level of learning motivation during students